HOTS Analysis of Students Reviewed from AQ Type PROPOMIMI Technical Assistance in Learning Differential Calculus - Fitriana Eka Chandra (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2019)
This research is a qualitative descriptive research that aims to describe High Order Thingking Skill (HOTS) students using PROPOMIMI technique. PROPOMIMI technique is a technique to make a mind map of a basic idea which will then be connected with various concepts that students have to create and solve a new problem. The subject of this study consists of 2 people, namely 1 person who has a low AQ and 1 person who has high AQ. From the result of the research, it is known that the highest HOTS is student with the type of AQ climbers and the lowest is the students with the type of AQ quitters. Keywords: HOTS, AQ, PROPOMIMI